Rancang Bangun Aplikasi Administrasi Proyek "Digitalisasi Dokumen" Pada CV. Smart Solusi Indonesia - Putra, Martinus Heri Anggara; Tanuwijaya, Haryanto; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV Smart Solution Indonesia (SSI) is a company focused on the provision of facilities and infrastructure of archives and archival processing services. Business processes company currently runs from sales manuals offer services over the media to the customer. A problem that often occurs in CV Smart Solution Indonesia at this time, the Project Manager often forget about the order that informed sales because theinformation only through the spiel. So the existing order can’tdirectly in the process. Project Manager of the difficulty in knowing the progress of the project because of the many projects that are being worked on. So a lot of tenants could not be completed on time. This problem resulted in the large number of complaints from customers so that the image of the SSI be bad and lost customers. The difficulty of knowing the progress of this project occur resulting from the recording of progress of project work is still done manually. The solutionis to use the administration application project "digitalization of documents" that functions to provide information about the progress of the project as well as the entire per project being worked on.